Nitric oxide and flavonoids are systemically induced by UV-B in maize leaves - Tossi, Vanesa Eleonora (2012)
Flavonoids are UV-B absorbing compounds whose concentration, increase in plant cells stimulated by UV-B irradiation. In this work, we characterized the systemic accumulation of flavonoids in maize seedlings irradiated with 3.3Wm-2 UV-B. Results indicate that both nitric oxide (NO) and flavonoids are systemically induced in UV-B-irradiated maize seedlings. Maize leaves pre-treated with the specific NO scavenger cPTIO, do not accumulate NO and flavonoids in response to UV-B. Whereas NO and flavonoids are accumulated in the mesophyll cells near to the leaf side receiving the UV-B irradiation, they are distributed in all tissues displaying the systemic response. Flavonoids and NO co-localize in UV-B irradiated maize leaves analyzed by images from epifluorescence microscopy. Chalcone synthase (CHS) and chalcone isomerase (CHI) genes are involved in the flavonoid biosynthetic pathway and their expression is systemically induced by UV-B in a NO dependent pathway. Finally, a functional approach demonstrates that maize leaves expressing the systemic response to UV-B show low cellular damage measured as ion leakage when they are challenged by a second round of irradiation.